(untitled) - Campbell, A. Malcolm (San Francisco, 2003)
A first textbook for upper-level undergraduates and first-year graduate students which combines integrated Web exercises with a problem-solving approach to train students in basic hands-on genomic analysis.
Keywords: Genomics,Proteomics,Bioinformatics,Bộ gen,Tin sinh học